PENGARUH PERSEPSI SISWA TENTANG GAYA MENGAJAR GURU DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR AKUNTANSI PADA PRORAM KEAHLIAN AKUNTANSI SISWA KELAS X DI SMKN 1 SAWAHLUNTO TAHUN AJARAN 2012/2013 - Deswita, Atika Prama; Akhirmen, Akhirmen; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2013)
ABSTRACTÂ This study aims to reveal the effect : students perceptions of teachers teaching styles on learning outcomes at the program Accounting Accounting skills class x students at SMK 1 Sawahlunto academic year 2012/2013 , the influence of students interest towards learning outcomes at the program Accounting Accounting skills in grade x SMK 1 Sawahlunto academic year 2012/2013 , the influence of students perceptions of teachers teaching styles and student interest in the learning outcomes of the program Accounting Accounting skills class x students at SMK 1 Sawahlunto academic year 2012/2013 .Type of research conducted in this research is descriptive quantitative approach Associative . The population is the total number of students in vocational classes x 1 Sawahlunto totaling 63 people . Sampling technique using proportional stratified random sampling technique which totaled 39 people.Data were collected through a questionnaire using a Likert scale that has been tested validity and reliability . The data analysis technique used is descriptive analysis and inductive analysis . To test the hypothesis used t test and f . Based on the results of t-test of hypothesis testing students perceptions of teachers teaching styles meaningful and positive impact on learning outcomes of Accounting , t test students interest in learning meaningful and positive impact on learning outcomes of Accounting . While the means test and a positive influence f between students perceptions of teachers teaching styles and student interest towards learning outcomes of Accounting . The amount of influence on students perceptions of teachers teaching styles and student interest in the learning outcomes of Accounting is 38.90 % and the remaining 61.10 % is influenced by other variables not included in the model in this study. Keywords : Student Perceptions of the teacher s teaching style , student interest , learning outcomes Accounting , multiple linear regression